Strata behavior at fully-mechanized coal mining and solid backfilling face - Yin, Wei (Springerplus, 2016)
Taking Ping Dingshan Coal Mine Group 12 as an example, this paper explains the system layout, key equipment and backfilling technology in detail. It probes into the characteristic of rock strata movement behavior and surface deformation above the gob area through in-site measurement method. The results show that as the overburden strata are effectively supported by the backfill body in mined out areas, there were no evident phenomena as first weighting or periodic weighting during mining process. Besides, influencing scope of advanced support pressure and the strata behavior degree were much smaller than that of the traditional methods of caving mining. Since overburden strata had been well supported by backfill body, it shows the posture of sinking slowly, only resulting in bending zone and minor fracture zone.